Enhancing immunotherapy through PD‐L1 upregulation: the promising combination of anti‐PD‐L1 plus mTOR inhibitors - Anna Hernández‐Prat; Alejo Rodriguez‐Vida; Laura Cardona; Mengjuan Qin; Oriol Arpí‐Llucià; Luis Soria‐Jiménez; Sílvia Menendez; Fabricio Gerel Quimis; Miguel Galindo; Edurne Arriola; Marta Salido; Nuria Juanpere‐Rodero; et al. (Molecular Oncology)
Immune checkpoint inhibitors (ICIs) targeting the programmed cell death protein 1 (PD‐1)/programmed cell death 1 ligand 1 (PD‐L1) pathway have transformed urothelial cancer (UC) therapy. The correlation between PD‐L1 expression and ICI effectiveness is uncertain, leaving the role of PD‐L1 as a predictive marker for ICI efficacy unclear. Among several ways to enhance the efficacy of ICI, trials are exploring combining ICIs with serine/threonine‐protein kinase mTOR (mTOR) inhibitors in different tumor types. The potential interaction between mTOR inhibitors and PD‐L1 expression in UC has not been well characterized. In our study, we investigated how phosphoinositide 3‐kinase (PI3K)/AKT/mTOR pathway inhibitors (TAK‐228, everolimus and TAK‐117) affect PD‐L1 expression and function in preclinical bladder cancer cell models. TAK‐228 increased cell surface levels of glycosylated PD‐L1 in all but one of the seven cell lines, regardless of baseline levels. TAK‐228 promoted the secretion of epidermal growth factor (EGF) and interferon‐β (IFNβ), both linked to PD‐L1 protein induction. Blocking EGF and IFNβ receptors reversed the TAK‐228‐induced PD‐L1 increase. Additionally, TAK‐228 enhanced IFN‐γ‐induced PD‐L1 expression and intracellular HLA‐I levels in some cells. TAK‐228‐treated bladder cancer cells exhibited resistance to the cytotoxic effects of peripheral blood mononuclear cells (PBMCs) and cluster of differentiation 8 (CD8)+ T cells. The addition of an anti‐PD‐L1 antibody diminished this resistance in T24 cells. Increased expression of PD‐L1 under TAK‐228 exposure was confirmed in patient‐derived explants (PDEs) treated ex vivo. These preclinical findings suggest that mTOR inhibition with TAK‐228 can increase PD‐L1 levels, potentially impacting the specific immune response against UC cells. This highlights the rationale for exploring the combination of mTOR inhibitors with ICIs in patients with advanced UC.